The NU champion : the story of the national bulldogs incredible season - Janine Patricia Robredo;Olivares, Rick (Manila, Philippines : National University, 2015)
"The following year, we set our sights on the Bulldogs winning the UAAP Men's basketball Championship in five years. We missed the projection in Season 76, the plan's fifth year. The Bulldogs which gained the number 1 position in the final four was eliminated. Disappointing and painfully."
Chapter 1 : The school of hard knocks -- Chapter 2 : A NU Era -- Hans Sy : The Bulldog's Booster -- Chapter 3 : Building a Champion -- Coach E is a winner and miracle worker -- Chapter 4 : An Unexpected Ending -- Moving Forward
Keywords: NATIONAL UNIVERSITY